Spatial Data Inventory and Collaboration System: A Web-GIS Development and Outreach Approach for Matesih Digital Village - Yusfia Hafid Aristyagama; Cucuk Wawan Budiyanto; Nurcahya Pradana Taufik Prakisya; Puspanda Hatta; Febri Liantoni; Rosihan Ari Yuana (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
Developing the potential of foster villages is often hindered by a lack of valid and integrated field data. Matesih Village in Karanganyar Regency possesses significant natural and economic potential, yet it remains under-explored by the research community. This study aims to develop a web-based GIS application as a spatial mapping medium for village potentials and problems to initiate the "Digital Village" concept. The system was developed using the prototyping method, which encompasses three main stages: preparation, application development, and socialization. This application is designed based on the Community of Practice (CoP) framework to facilitate interaction and shared learning between village officials as data providers and researchers as solution providers. The results of this community service indicate that the developed GIS application supports the digitization of village’s potential data and has been socialized to village officials to support data-driven policy-making.